Proteção internacional do direito ao trabalho da pessoa com deficiência - Leal, Carla Reita Faria (2008)
In the current paper, a study about the international rules of protection for the people with disability rights at work is developed. First, it is explained which terminology is more appropriated to define the people with disability. Its concept is also determined, based on the standards provided by the international Organizations, national law specialists, and some countries legal principles. Next, it is analysed the treatment provided to the people with disability through the history, aiming to understand their place in the society nowadays. Then, it is studied the factual and legal foundation that justify the action of the State and society, for the protection of this part of the population. The rules provided for the implementation of the people with disability right at work by the UN (United Nations), ILO (International Labour Organization), and OAS (Organization for the American States) are analysed as the main aim of this paper. The issue is also studied according to the principles of countries such as Italy, Spain, Portugal and Brazil. It is examined the Labour General Councel action to make sure that the people with disability have their right at work respected. It is concluded that for the effectiveness of democracy it is necessary to guarantee conditions for decent life to all citizens. Thus, it is necessary to provide the people with disability with opportunity of full and effective participation in the construction of a free, fair and generous society